PDMS-enhanced slowly degradable Ca-P-Si scaffold: Material characterization, fabrication and in vitro biocompatibility study. (June 2021) - Wu, Tao; Li, Zhanpeng; Chen, Yadong; Liu, Qiang; Zhang, Jingshu; Yu, Kun; Wang, Yu; Wang, Zhiguo; Gong, Tianxing
A slowly degradable bone scaffold can well maintain the balance between new bone regeneration and scaffold resorption, esp. for seniors or patients suffering from pathological diseases, because too fast degradation can lead to the loss of long-term biological stability and result in scaffold failure. In this present study, calcium phosphate silicate (CPS) and polydimethylsiloxane (PDMS) were blended in different ratios to formulate slurries for scaffold fabrication. The effects of crosslinked PDMS on the CPS material properties were first characterized and the most viable formulation of CPS-PDMS slurry was determined based on the aforementioned results to 3D fabricate scaffolds. The biocompatibility of CPS-PDMS was further evaluated based on the scaffold extract's cytotoxicity to osteoblast cells. Furthermore, real-time PCR was used to investigate the effects of scaffold extract to increase osteoblast proliferation. It is showed that the crosslinked PDMS interfered with CPS hydration and reduced both setting rate and compressive strength of CPS. In addition, CPS porosity was also found to increase with PDMS due to uneven water distribution as a result of increased hydrophobicity. Degradation and mineralization studies show that CPS-PDMS scaffold was slowly degradable and induced apatite formation. In addition, the in vitro analyses show that the CPS-PDMS scaffold did not exert any cytotoxic effect on osteoblast cells but could improve the cell proliferation via the TGFβ/BMP signaling pathway. In conclusion, CPS-PDMS scaffold is proved to be slowly degradable and biocompatible. Further analyses are therefore needed to demonstrate CPS-PDMS scaffold applications in bone regeneration.